2012
DOI: 10.1103/physreve.86.066404
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dust-acoustic solitary waves in strongly coupled dusty plasmas

Abstract: Dust-acoustic waves are investigated in a three-component plasma consisting of strongly coupled dust particles and Maxwellian electrons and ions. A fluid model approach is used, with the effects of strong coupling being accounted for by an effective electrostatic "pressure" which is a function of the dust number density and the electrostatic potential. Both linear and weakly nonlinear cases are considered by derivation and analysis of the linear dispersion relation and the Korteweg-de Vries equation, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
6
32
0
Order By: Relevance
“…This is the same coefficient that was found in Ref. [18], in which solitons were studied. If we instead had neglected the perturbations and assumed T = T 0 , we would obtaiñ and if we neglect the electrostatic temperature terms completely, we obtainà = − 3 + 2c 2 2 .…”
Section: B Nonlinear Shockssupporting
confidence: 67%
See 1 more Smart Citation
“…This is the same coefficient that was found in Ref. [18], in which solitons were studied. If we instead had neglected the perturbations and assumed T = T 0 , we would obtaiñ and if we neglect the electrostatic temperature terms completely, we obtainà = − 3 + 2c 2 2 .…”
Section: B Nonlinear Shockssupporting
confidence: 67%
“…[18] we theoretically investigated weakly nonlinear dust-acoustic solitary waves in a complex plasma in which the dust particles are strongly coupled, with the effects of strong coupling being accounted for by the electrostatic temperature approach. To account for local variations in electrostatic temperature in the vicinity of a wave, we introduced the concept of electrostatic temperature perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…All of these works are valid in the absence of the effective dust temperature [20][21][22][23][24][25][26][27] (due to the strong electrostatic interactions among the highly negatively charged dust grains) and the polarization force 20,23,28-37 (i.e., the force due to the polarized Debye sheath). However, it has been shown that in the particular cases, for the low frequency DA waves these effects are quite important and need to be taken into account.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that pair-ion plasmas with positively charged dusts support DIA solitons only of the rarefactive type. There are, however, a number of recent works dealing with the nonlinear properties of solitary waves [12][13][14][15][16][17][18][19][20][21] , electrostatic ion-cyclotron waves 22 shocks 23 in other plasma environments.…”
Section: Introductionmentioning
confidence: 99%